Strategies to develop sociopragmatic competence in learners of english as forgeign language - Uribe Martínez, Liz Maleni (2015)
In this study, it was noticed that the English learners of the fifth level in the Language Center (UANL) need to develop more their sociopragmatic competence when requesting things. This means that the learners can produce speech acts, but they do not know how to use the different sentences they create according to the context and situation. The learners are able to create grammatically correct sentences (since they use strategies to create them) when they want to request something, but they are unable to use them properly when communicating orally. This research aims to investigate and propose learning strategies to develop the sociopragmatic competence of the learners.